Applied Computing & Information Technology - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This edited book presents scientific results of the 3nd International Conference on Applied Computing and Information Technology (ACIT 2015) which was held on July 12-16, 2015 in Okayama, Japan. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the numerous fields of computer science and to share their experiences and exchange new ideas and information in a meaningful way. Research results about all aspects (theory, applications and tools) of computer and information science, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence